O idoso tem direitos - NOSTÓRIO, Aline; BELISARIA, Douglas; GONÇALVES, Fabio; CELESTINO, Leticia; CORDEIRO, Sirley (172, 2015)
Segundo os últimos dados da ONU (organização das nações unidas), a população mundial deve aumentar dos 6 bilhões no ano de 2000, para 10 bilhões em 2050. No mesmo período o número de pessoas como mais de 60 anos deve triplicar passando de 600 milhões para 2 bilhões, ou seja, quase 25% da população do planeta terá 60 anos ou mais. Estabelecido esta problemática o Estatuto do Idoso surgiu no Brasil para garantir direitos essenciais para capacitação socialização que afetam a alta estima, emoções e a predisposição em viver sua vida de forma agradável. É um equívoco achar que os idosos não são criativos e capazes, pois muitos dos grandes nomes da história como artistas, músicos e cientistas produziram suas maiores obras após os 60 anos.

According to the latest data from the UN (organization of the united nations), the world population is expected to increase from 6 billion in the year 2000 to 10 billion in 2050 In the same period the number of people over 60 years old is expected to triple from 600 million to 2 billion, that is, almost 25% of the planet's population will be 60 years of age or older. Having established this problem, the Elderly Statute appeared in Brazil to guarantee essential rights for empowerment and socialization that affect high esteem, emotions and the predisposition to live your life in a pleasant way. It is a mistake to think that the elderly are not creative and capable, as many of the great names in history as artists, musicians and scientists produced their greatest works after the age of 60.
Keywords: Direito do idoso; Gestão e Negócios